Ovarian cancer tumor immune microenvironment and its clinical trial implications - Barbora Vavrušáková; Renata Bartošová; Michal Hendrych; Tomáš Kazda; Lukáš Moráň; Marek Svoboda (Discover Oncology, 2026)
Abstract Ovarian cancer is the most lethal gynecologic malignancy, primarily because of late-stage diagnosis, rapid disease progression, and marked molecular and immunologic heterogeneity. It remains the leading cause of gynecologic cancer-related death, affecting approximately 1 in 70 women in developed countries over their lifetimes. Tumor development and progression are orchestrated within the tumor immune microenvironment, a dynamic and complex structural niche that supports malignant transformation and immune evasion of the tumor. In this narrative educational review, we aim to provide a comprehensive overview of recent advances in the understanding of ovarian cancer pathogenesis, the molecular mechanisms driving tumor progression, and the multifaceted role of the immune system in disease development and therapeutic response. Moreover, we summarize recent clinical trials targeting key molecular drivers and components of the tumor immune microenvironment, including immunotherapeutic and targeted approaches. Personalized medicine, guided by integrative genomic and transcriptomic profiling, has become increasingly vital for patient stratification and treatment selection. Ultimately, a shift toward highly individualized, mechanism-based therapeutic strategies is essential to improve clinical outcomes and survival in ovarian cancer.